VD_FINDINFO Jug / 2019 / 262 vom 27. März 2018 - VD Tribunal cantonal (2018)
LÉSÉ, CAPACITÉ D'ÊTRE PARTIE, PARTIE À LA PROCÉDURE, DIMINUTION EFFECTIVE DE L'ACTIF, TRIBUNAL FÉDÉRAL | 164 ch. 1 CP, 115 CPP (CH)